Monitoring circulating tumor DNA liquid biopsy in stage III BRAF-mutant melanoma patients undergoing adjuvant treatment - Sara Marchisio; Alessia Andrea Ricci; Gabriele Roccuzzo; Eleonora Bongiovanni; Erika Ortolan; Luca Bertero; Enrico Berrino; Valentina Pala; Renata Ponti; Paolo Fava; Simona Osella-Abate; Silvia Deaglio; et al. (Journal of Translational Medicine)
Abstract Background The introduction of adjuvant therapies for patients with resected cutaneous melanoma (CM) has increased the need for sensitive biomarkers for risk stratification and disease monitoring. This study aims to investigate the utility of circulating tumor DNA (ctDNA) assessment in predicting and reflecting disease status during adjuvant therapy. Methods We enrolled 32 patients with resected BRAF-mutated stage III CM receiving adjuvant targeted therapy or immunotherapy. Plasma samples of patients were collected at the baseline (treatment initiation) and during the therapy, and BRAF-mutated ctDNA was quantified by droplet digital PCR (ddPCR). Results Baseline ctDNA was detected in 11/32 (34.4%) patients and predicted postoperative high risk of relapse [HR 3.79, 95% CI 1.20–12.00, p = 0.023]. The three-year overall survival (OS) rate was 54.6% (95% CI 22.9–77.9) versus 95% (95% CI 69.5–99.3) in ctDNA-positive and negative groups, respectively, with significantly worse OS for ctDNA-positive patients [HR 7.92, 95% CI 1.56–40.36, p = 0.013]. Among the baseline ctDNA-positive group (high-risk patients), longitudinal ctDNA detection during adjuvant therapy reflected the clinical outcomes. Only non-relapsing patients cleared their plasma ctDNA by the end of the treatment, while persistent ctDNA detection provided early evidence of disease recurrence. Conclusions ctDNA detection shows promising results in the post-operative setting for identifying cutaneous melanoma patients at the highest risk of relapse and for real-time monitoring of patients’ clinical status and treatment response.